WAYS TO INCREASE THE EFFICIENCY OF PERSONNEL MANAGEMENT OF THE RESTAURANT ENTERPRISE - GARASYMLIUK, MARIIA; DATSIV, OLGA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article is devoted to outlining ways to improve the personnel management system in the field of corporate development of restaurant enterprises, which includes the introduction of innovative technologies of restaurant service, employee training programs to grow professional competencies and personal psychological characteristics, career advancement for the best employees. It is determined that the basic principle of personnel management in restaurants is systemic, so the search for ways to improve management should include consideration of this process as a holistic system, taking into account the relationships between its elements. It is offered to pay special attention to management of processes of communication of the personnel with clients, development of adequate professional behavior in conflict situations. It is proposed to take into account the requirements for staff from the standpoint of consumers, which provide speed and high quality service and the appropriate level of communication, from the standpoint of owners – competencies and knowledge, personal qualities and consumer-oriented behavior, from the standpoint of staff - skills, abilities and motivation. Motivational programs are proposed to focus on the formation of employees’ desire to acquire new knowledge and acquire new skills. To increase the efficiency of personnel management, it is proposed to develop strategies for personnel development and differentiate by strategic and tactical goals. It is proposed to introduce a system of key performance indicators for control in terms of tactical and strategic plans for staff development and the establishment of intermediate control with control points of assessment. It is proposed to evaluate the performance of each category of employees within their functional responsibilities, as well as indicators of staff development of the enterprise as a whole. It is proposed to include qualification, personal, competence and value characteristics, efficiency of activity, reserves of growth of production and social efficiency in the assessment of the efficiency of personnel management of restaurant enterprises. Further research should focus on the study of customer management of restaurant staff.